Severity of Neuropsychiatric Symptoms and Distress in Dementia among Older People in Central Africa (EPIDEMCA Study). Issue 1 (4th November 2019) - Yoro‐Zohoun, Inès; Houinato, Dismand; Nubukpo, Philippe; Mbelesso, Pascal; Ndamba‐Bandzouzi, Bébène; Clément, Jean‐Pierre; Dartigues, Jean‐François; Preux, Pierre‐Marie; Guerchet, Maëlenn; ,
Abstract : OBJECTIVES: Neuropsychiatric symptoms are common in dementia. Limited data are available concerning their association with dementia in developing countries. Our aim was to describe the severity of neuropsychiatric symptoms among older people, evaluate the distress experienced by caregivers, and assess which neuropsychiatric symptoms were specifically associated with dementia among older adults in Central Africa. DESIGN: This study is part of the EPIDEMCA program, a cross‐sectional multicenter population‐based study. SETTING: The EPIDEMCA program was conducted from November 2011 to December 2012 in urban and rural areas of the Central African Republic and the Republic of the Congo. PARTICIPANTS: Participants were older people (≥65 y) included in the EPIDEMCA program who underwent a neuropsychiatric evaluation. The sample included overall 532 participants, of whom 130 participants had dementia. MEASUREMENTS: Neuropsychiatric symptoms were assessed with the brief version of the Neuropsychiatric Inventory including the evaluation of severity and associated distress. Diagnostic and Statistical Manual of Mental Disorders, 4th ed., Text Revision, criteria were followed to diagnose dementia. A logistic regression model was used to identify associated neuropsychiatric symptoms. RESULTS: The prevalence of neuropsychiatric symptoms was 89.9% (95% confidence interval = 84.6‐95.1) among people living with dementia. The overall median severity score for neuropsychiatric symptoms was 9 [interquartile range [IQR] = 6‐12], and the overall median distress score was 7 [IQR = 4‐10]. Overall median scores of both severity and distress were significantly increased with the number of neuropsychiatric symptoms, the presence of dementia, and dementia severity. Depression, delusions, apathy, disinhibition, and aberrant motor behavior were associated with dementia after multivariate analysis. CONCLUSION: This report is one of the few population‐based studies on neuropsychiatric symptoms among older people with dementia in Sub‐Saharan Africa and the first one evaluating the severity of those symptoms and distress experienced by caregivers. Individual neuropsychiatric symptoms were strongly associated with dementia in older people and require great attention considering their burden on populations. J Am Geriatr Soc 68:180–185, 2019